Vander's human physiology - Widmaier, Eric P.
The tenth edition of this classic text has been entrusted into the capable hands for the 2nd time to a dynamic author team. Eric Widmaier, Hershel Raff, and Kevin Strang have taken on the challenge of maintaining the strengths and reputation that have long been the hallmark of Human Physiology: The Mechanisms of Body Function. The fundamental purpose of this textbook has remained undeniably the same: to present the principles and facts of human physiology in a format that is suitable for undergraduates regardless of academic background or field of study. Human Physiology, tenth edition, carries on the tradition of clarity and accuracy, while refining and updating the content to meet the needs of today's instructors and students. The tenth edition features a streamlined, clinically oriented focus to the study of human body systems